Analisis Faktor-Faktor yang Mempengaruhi Pembiayaan Bagi Hasil Pada Bank Umum Syariah Indonesia - Rizki Dwi Haryanti; Titin Agustin Nengsih; Bambang Kurniawan (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This study uses independent variables, namely FDR, TPF, ROA. The dependent variable used is Profit Sharing Financing. The population in this study is Indonesian Islamic Commercial Banks. Samples were selected using purposive sampling method. In this study, there were 11 Islamic Commercial Banks with a research period of 5 years. The sample used in this study amounted to 55. The analytical method used in this research is multiple linear regression analysis which is processed using SPSS 25 and Microsoft Excel applications. The results of this study partially show that FDR, DPK, and ROA have no effect on the financing of profit-sharing financing, while the DPK variable has a significant effect on profit-sharing financing. Based on the research results, the ratio of FDR, DPK, and ROA simultaneously has a significant effect on profit sharing financing at Indonesian Islamic Commercial Banks. Based on the results of simultaneous and partial research, it is concluded that the most dominant influence on profit sharing financing in Indonesia in this study is the DPK variable.